Antioxidant and Anti-Inflammatory Activities of Biofield Energy Treated Proprietary Test Formulation in Brain Tissues in Cecal Slurry, LPS and E. Coli-Induced Systemic Inflammatory Response Syndrome (SIRS) in Sprague Dawley Rats - Kumar Trivedi Mahendra; Branton Alice; Trivedi Dahryn; Jana Snehasis (International Journal of Global Health, 2021)
LPS and E. Coli-Induced SIRS in Sprague Dawley Rats